2001
DOI: 10.1159/000064600
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Deep Brain Stimulation Surgery

Abstract: Although technological advances have reduced device-related complications, DBS surgery still carries a significant risk of transient and permanent complications. We report our experience in 86 patients and 149 DBS implants. Patients with Parkinson’s disease, essential tremor and dystonia were treated. There were 8 perioperative, 8 postoperative, 9 hardware-related complications and 4 stimulation-induced side effects. Only 5 patients (6%) sustained some persistent neurological sequelae, however, 26 of the 86 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(172 citation statements)
references
References 6 publications
5
160
2
5
Order By: Relevance
“…The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96][97]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96][97]…”
Section: Resultsmentioning
confidence: 99%
“…Despite reports of the safety and efficacy of DBS for movement disorders, 33,113 this surgery is not without adverse events, which may relate to the surgical procedure, implanted hardware, or the stimulation itself. 7 More recently, pilot studies and small clinical trials have demonstrated the efficacy and safety of DBS of the NAc in neuropsychiatric diseases such as obsessive-compulsive disorder 32 and major depression that are refractory to treatment. 95 To date, however, no clinical trials have been performed for morbid obesity.…”
mentioning
confidence: 99%
“…Eye lid apraxia is a non-paralytic motor abnormality characterized by difficulty in initiating opening of the eyelids [7,8]. Premotor control of lid-eye coordination by extrapyramidal and mesencephalic circuitries has been suggested and dopaminergic involvement was further substantiated by analysis of blinking rates in patients with PD [9].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal hardware programming can be challenging in some cases, as side effects may interfere with stimulation parameters required for sufficient control of motor symptoms [3,4]. Eyelid Apraxia, defined as inability to voluntarily initiate opening of eyelids [5], is one of limiting adverse effects which has been reported in 1.8 to 30% of the patients after STN DBS and management of the eyelid apraxia event was mainly relied on medical treatment [6][7][8].…”
Section: Deep Brain Stimulation (Dbs) Of the Subthalamic Nucleus (Stn)mentioning
confidence: 99%
“…They described perioperative complications in eight patients (hemorrhages, confusion, and seizures) and longterm postoperative complications in eight patients (delayed hematoma, behavioral changes, confusion, apraxia of eyelid opening, and peripheral nerve injury). Hardware-related issues were studied in nine patients (DBS electrode failure, extension wire failure, pulse generator malfunction, and pain over pulse generator) and stimulation-induced side effects were diagnosed in four patients (dysarthria, facial contraction, and confusion) [9].…”
Section: Technique and Physiological Considerationsmentioning
confidence: 99%